The Impact of Trust, Convenience, and Financial Literacy on Purchasing Decision Using Paylater (Study on Paylater Users in Greater Surabaya) - Widya Kusuma Dewi; Detak Prapanca; Sriyono Sriyono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Paylater is a financial service that offers online loans, facilitating transactions with an installment system or full payment the next day. The purchase decision to use paylater is greatly influenced by the level of trust, convenience, and financial literacy. The unwise use of paylater can have a potential for consumptive behavior. This study aims to identify factors that influence consumer decisions, and provide an overview of the role of trust, ease of access, and financial understanding in shaping purchasing decisions using paylater. In this study, a quantitative method was used and the number of samples was 100 respondents. The population in this study is paylater users in Greater Surabaya. The sampling method uses a non-probability sampling technique with a purposive sampling technique. The data sources used come from primary and secondary data. Primary data sources are obtained through the dissemination of questionnaires through Google Forms while secondary data sources come from books, journals, and articles from previous research. The data analysis technique uses Partial Least Square (PLS) version 4.0. The results of this study show that (1) Trust has a significant positive effect on purchase decisions. (2) Convenience has a significant positive effect on purchase decisions. (3) Financial Literacy has a significant positive effect on purchase decisions.